1980
DOI: 10.2172/6682455
|View full text |Cite
|
Sign up to set email alerts
|

Tritium: An analysis of key environmental and dosimetric questions

Abstract: Printed in the UniH'd Stfltes of Ameri<.a. AVJifable from the D'~pi1rtmdnt of Enorgy Tcchl'icil.! lniolfl'wt;on Cemer I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Tritium has a 18 keV (5.7 keV average) beta particle emission so that any change in the w R for low-energy beta particles would affect tritium discharge concentration and intake limits by a similar factor. A value of 1.0 does not appear to be appropriate for its radiation (Bond and Feinendegen 1966, Feinendegen 1967, Lambert 1969, NCRP-062 1979, Till et al 1980a, 1980b, Killough 1982, ICRU-40 1986, Straume and Carsten 1993 and Report 9-1 of CERRIE (2004), HPA 2007. Based upon review of the biological effects data, officials of the ICRP have published a rationale for its approach of retaining 1.0 (Cox, Menzel and Preston (ICRP) 2008).…”
Section: Radiation Linear Energy Transfer Relative Biological Effecti...mentioning
confidence: 99%
“…Tritium has a 18 keV (5.7 keV average) beta particle emission so that any change in the w R for low-energy beta particles would affect tritium discharge concentration and intake limits by a similar factor. A value of 1.0 does not appear to be appropriate for its radiation (Bond and Feinendegen 1966, Feinendegen 1967, Lambert 1969, NCRP-062 1979, Till et al 1980a, 1980b, Killough 1982, ICRU-40 1986, Straume and Carsten 1993 and Report 9-1 of CERRIE (2004), HPA 2007. Based upon review of the biological effects data, officials of the ICRP have published a rationale for its approach of retaining 1.0 (Cox, Menzel and Preston (ICRP) 2008).…”
Section: Radiation Linear Energy Transfer Relative Biological Effecti...mentioning
confidence: 99%
“…Despite the ICRP recommendation in effect to use a Q of 1 instead of the previously recommended value of 1.7 for tritium beta radiation, some radiobiological evidence at low dose rates in recent years has suggested that a Q greater than 1 relative to gamma ray effects is appropriate (Refs. 6,20). Human data are not available to distinguish between these two values, and many references and inquiries have shown that action levels and dose calculations in use in the United States for radiation protection purposes are still following derived urinary excretion values based on a Q of 1.7 (Refs.…”
Section: Selection Of Q (Quality Factor Formerly Qf)mentioning
confidence: 99%
“…6, 32), the estimate that doses to organic long-term compartments may be up to 1.5 times that calculated for body water (Refs. 6,34), and the desirability of avoiding unnecessary perturbations in alreadyfunctioning bioassay programs, it seems reasonable to accept the ICRP (Ref. The dose rate to a mass m in grams containing A pCi of radioactivity is (Ref .…”
Section: Selection Of Q (Quality Factor Formerly Qf)mentioning
confidence: 99%
“…Other experiments are being carried out, mainly at Oak Ridge National Laboratory (ORNL), to resolve uncertainties in the data or in the techniques used to observe the amount of tritium and whether there are any other source terms not taken into account. The results of this experiment are shown in Table 2 (Till, et al 1980), which compares the calculated and experimental yields. (a) Based on irradiations in the fast flux of EBR-II (Buzzelli et al, 1976;Buzzelli and Langer, 1977).…”
Section: Fissionmentioning
confidence: 99%